A LEGAL ANALYSIS OF THE CIVIL LIABILITY OF PT PETER METAL TECHNOLOGY INDONESIA REGARDING THE RELEASE OF THE RADIOACTIVE SUBSTANCE CESIUM-137: PERSPECTIVES FROM ENVIRONMENTAL LAW AND THE INDONESIAN CIVIL CODE - Max Doan Simanjuntak; Sulastri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The case of the spread of radioactive Cesium-137 (Cs-137) that polluted the Modern Cikande Industrial Area, Banten, which originated from metal scrap of PT Peter Metal Technology Indonesia (PMT) has posed a serious threat to the environment and the surrounding community. This study aims to analyze the form of civil liability of PT PMT for the spread of radioactive substances viewed from the perspective of Environmental Law and the Civil Code (KUHPerdata). This study uses a normative legal research type (normative juridical) through a statutory approach, a case approach, and a conceptual approach. Data collection was carried out by means of a literature study and analyzed using qualitative methods. The results of the study indicate that the spread of Cs-137 is subject to the principle of strict liability as regulated in Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH), where companies that manage high-risk hazardous and toxic materials (B3) are held absolutely responsible without the need to prove any element of fault. PT PMT's civil liability is based on Article 1365 of the Civil Code concerning Unlawful Acts (PMH) and Article 87 of the Environmental Management Law (UUPPLH), which implements the polluter pays principle. Therefore, PT PMT is obligated not only to pay compensation to injured parties but also to bear all costs of decontamination and environmental restoration. However, the effectiveness of this civil sanction depends heavily on scientific proof of causality and the results of investigations by authorized technical agencies, such as BAPETEN and BRIN.